2014
DOI: 10.1186/1477-7819-12-230
|View full text |Cite
|
Sign up to set email alerts
|

Patient age is related to decision-making, treatment selection, and perceived quality of life in breast cancer survivors

Abstract: BackgroundPatients with breast cancer must choose among a variety of treatment options when first diagnosed. Patient age, independent of extent of disease, is also related to quality of life. This study examined the impact of patient age on treatment selected, factors influencing this selection, and perceived quality of life.MethodsA 62-question survey evaluating breast cancer treatment and quality of life was mailed to breast cancer survivors. Responses were stratified by age (<50, 50-65, >65 years) and exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 33 publications
1
31
1
Order By: Relevance
“…International studies are in contrast to the findings of the present study, and indicate the occurrence in the age group over 50 years, women's mean age of 61.8 years in Sweden (12) and 58 years in the United States. (13) In addition to the age group, other factors deserve health professionals' attention, such as educational level and socioeconomic status. In the private institution, several women have studied more than 12 years, but in the public institution, many women studied less than nine years, which demonstrates the educational level difference between women with breast cancer in chemotherapy treatment at the two institutions.…”
Section: Discussionmentioning
confidence: 99%
“…International studies are in contrast to the findings of the present study, and indicate the occurrence in the age group over 50 years, women's mean age of 61.8 years in Sweden (12) and 58 years in the United States. (13) In addition to the age group, other factors deserve health professionals' attention, such as educational level and socioeconomic status. In the private institution, several women have studied more than 12 years, but in the public institution, many women studied less than nine years, which demonstrates the educational level difference between women with breast cancer in chemotherapy treatment at the two institutions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been stated that young patients have more aggressive tumor biology and worse oncologic outcomes than their older counterparts (1,3). In addition,it has been shown that the age of patients with breast cancer influencedthe choice of treatment (5). The limit that defines young age is uncertain in one study, it was published that the age limit for young people should be 35 years (6).…”
Section: Introductionmentioning
confidence: 99%
“…International studies oppose to the findings of this research and point the occurrence of breast cancer in an age group older than 50 years old, with average age among Swedish women of 61.8 years (Hoyer et al, 2011), 57 years in Chile (Irarrázaval et al, 2013), 58.4 years in France (Anota et al, 2014), and 58 years in the United States (Sio et al, 2014).…”
Section: Resultsmentioning
confidence: 80%
“…On the other hand, a study conducted in the United States evidenced mean scores between 69% and 90%, denoting that the women were coping better when it comes to their body image (Sio et al, 2014). In France, although evidenced mean values were high, they showed a decline after the start of the treatment (from 90 to 70%), indicating impairment of QL due to chances caused by the therapy (Anota et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation